Chronic small intestinal helminth infection perturbs bile acid homeostasis and disrupts bile acid signaling in the murine small intestine - Lane, Jenna M.; Brosschot, Tara P.; Gatti, Dominique M.; Gauthier, Courtney M.; Lawrence, Katherine M.; Pluzhnikova, Victoria; Reynolds, Lisa A. (Frontiers in Parasitology, 2023)
Intestinal helminths have evolved an abundance of immunomodulatory mechanisms to ensure long-lived infections in mammalian hosts. To manipulate mammalian immune responses helminths can directly produce immunomodulatory molecules, but helminth infection can also elicit functional changes in the intestinal microbiome which can impact immune functioning. Here we examined how bile acids (BA)s, a group of host-produced, microbiota-modified immunomodulatory metabolites, were altered in abundance and composition during a murine small intestinal helminth infection. We found that murine helminth infection resulted in consistently reduced concentrations of specific taurine-conjugated primary BAs (T-α-MCA and T-CDCA) in the small intestinal luminal contents of mice. BA transporters facilitate the uptake of BAs from the small intestinal lumen, allowing BAs to engage with nuclear BA receptors, and helminth infected mice showed reduced expression of genes encoding basal BA transporters in the small intestine. Finally, we report that there is reduced signaling through the nuclear BA receptor FXR in both the proximal small intestine and ileum of mice during small intestinal helminth infection. Together, our data reveal disruptions to BA homeostasis and signaling in the small intestine during helminth infection. As BAs are known to impact many aspects of mucosal physiology and immunity, examining the functional consequences of BA disruptions during helminth infection will be an important avenue for future research.